THE EVALUATION OF WATER LEVEL ELEVATION DESIGN OF SEI BATANG SERANGAN TOLL BRIDGE ON SEI BATANG SERANGAN RIVERSIDE - Telaumbanua, Elva Putri Octaviani; Sinaga, Marta Uli; Indrawan, Ivan; Sembiring, Ir. Robi Arianta (jfpublisher, 2023)
Hydrological analysis is conducted to determine the rainfall discharge that can be accommodated by the river with various specific return periods and hydraulic analysis to examine the water level that impacts the toll bridge that passes through the Sei Batang Serangan river. Therefore, this research was conducted to calculate the design flood discharge for the return period of 2, 5, 10, 25, and 50 years; and the water level elevation of Sei Batang Serangan toll bridge in the Sei Batang Serangan riverside. Based on hydraulic analysis using the HEC-RAS 5.0 program from steady flow data, the maximum water level elevation is at River Sta 5+00 of 10.52 m in a 50-year return period, and the minimum water level elevation is at River Sta 2+00 of 4.45 m in a 2-year return period. Thus, based on the flood water level of 12.691 meters, the Sei Wampu toll bridge area does not have flood inundation because the water level elevation value does not exceed the flood water level value (TMA < MAB). Meanwhile, from the results of the steady flow data analysis, it can be concluded that no flooding occurred at the Sei Batang Serangan toll bridge in the Sei Batang Serangan riverside at a known return period.